Inflammatory cytokines, oxidative and antioxidative stress levels in patients with diabetic macular edema and hyperreflective spots. Issue 5 (September 2021) - Sabaner, Mehmet Cem; Akdogan, Muberra; Doğan, Mustafa; Oral, Ayse Yesim; Duman, Resat; Koca, Tulay; Bozkurt, Erhan
Purpose: To determine the levels of serum oxidative, antioxidative markers and inflammatory cytokines in patients diagnosed with diabetic macular edema (DME) whose hyperreflective spots (HRS) were detected by optical coherence tomography (OCT). Methods: In this prospective cross-sectional clinical study included a total of 88 patients; 31 patients (group-1) with DME and HRS detected by OCT, 29 patients (group-2) with DME without HRS, and 28 patients (group-3) diagnosed with diabetes mellitus (DM) without any diabetic retinopathy findings. The main outcomes were best-corrected visual acuity (BCVA), CMT (central macular thickness), CMV (central macular volume), TMV (total macular volume), CT (choroidal thickness), serum TAS (total antioxidant status), TOS (total oxidant status), VEGF (vascular endothelial growth factor), FGF (fibroblast growth factor) and IL-1b levels. OCT parameters and biochemical measurements were compared statistically between the three groups. Results: A total of 88 patients (43 females (48.9%) and 45 males (51.1%)) were included in the study. The mean age was 56.29 ± 9.23 years. There was no difference between the three groups in age-and-sex. In group-1 and 2, BCVA(LogMAR) was statistically higher than group 3. CMT, CMV, TMV, TAS, TOS, VEGF and FGF were significantly higher in group-1 than in group-3. CMT, CMV, TMV, VEGF and FGF were significantly higher in group-2 than group 3. TOS and VEGF were significantly higher in group-1 than group-2. Conclusions: This study demonstrates that in patients with DME and HRS, TOS and VEGF levels were higher than those without HRS. Hence, hyperreflective spots may be an inflammatory biomarker.